Effects of wearing an ankle brace on ground reaction forces during jumps in basketball game simulation - Castro, Alex, 1990- (2021)
Abstract: Preclinical evidence suggests that caloric restriction is an effective therapy for a number of cardiovascular insults. Whether caloric restriction has cardio-protective effects in humans is not well understood. The aim was to systematically review and meta-analyze human randomized control trials (RCTs) testing the effect of caloric restriction on blood pressure (BP) and cardiovascular function. A systematic review was performed using Medline, EMBASE, CINAHL (up to June 2017) to search for RCTs of adults receiving a calorie-restricted intervention versus a control/standard diet. Random-effect meta-analyses were performed to calculate weighted mean difference and 95% CI. Thirty-two RCTs with 1722 participants assessing BP (n ¼ 29 studies), heart rate (n ¼ 10), VO2peak (n ¼ 8), muscle sympathetic nerve activity (MSNA, n ¼ 4), and endothelial function (n ¼ 4) were included. Calorie-restricted interventions lasting 1e4 weeks had the largest effect on systolic (5.5 mmHg, p < 0.001, 95% CI: 3.8, 7.1) and diastolic (2.9 mmHg, p ¼ 0.005, 95% CI: 5.0, 0.9) BP, but no effect on HR. Interventions lasting 1.5e6 months had similar effects on BP, and reduced HR (4.4 beats/minute, p < 0.001, 95% CI: 6.1,-2.8). Relative VO2peak improved (1.8 mL/kg/min, p < 0.001, 95% CI: 1.3, 2.2). There were also potential positive effects on MSNA and endothelial function. The effect of 1e4 weeks of calorie restriction on BP was similar to that expected with medications, and larger than that reported for other lifestyle interventions or supplements. Cardiovascular risk could be further reduced by caloric restriction lasting up to six months to lower heart rate and improve VO2peak.